Survival Analysis of Kidney Failure Patients Using the Kaplan Meier Method and Log-Rank Test: Survival Analysis of Kidney Failure Patients Using the Kaplan Meier Method and Log-Rank Test - Febrianti, Fatika Lovina; Firdatul Fahria; Siti Hamidah Ardhy; Rahma Nurmalita; Suci Laeliyah; Muhammad Rifqy Ardiansyah; Ihsan Fathoni; M. Al Haris (Statistics Department, Universitas Islam Indonesia, 2025)
Kidney failure is a global health issue that continues to rise, impacting patients' quality of life and placing significant pressure on healthcare systems. This study aims to analyze the factors influencing the survival probability of kidney failure patients using the Kaplan-Meier method and the log-rank test. Medical records from 106 kidney failure patients treated at Hasanuddin Hospital between 2018 and 2020 were used to examine the effects of age, gender, and disease severity on survival outcomes. The Kaplan-Meier analysis revealed that patients aged ≤ 50 years, females, and those with chronic conditions had better survival probabilities. However, the log-rank test indicated that survival differences based on these three variables were not statistically significant (p-value > 0,05). These findings provide an initial understanding of the survival patterns of kidney failure patients and highlight the need for further research with larger sample sizes or more advanced methods to support the development of personalized care strategies and improve patients' quality of life.